Arduino based mini scada for power distribution system relay control - Habib Muharry Yusdartono; Andik Bintoro; Dahlan Abdullah; Badriana Badriana; Fitria Priyulida (Journal Geuthee of Engineering and Energy, 2026)
This study aims to develop  a mini SCADA system  as a simpler and more affordable alternative solution for educational and research purposes, especially in the control of relays in distribution system modules. Design and implement  of a mini SCADA prototype are able to control the relay in real-time while evaluating the performance of the system in terms of response speed, control accuracy, and operational reliability. The research adopts both quantitative and qualitative approach with laboratory experiment methods at Malikussaleh University, utilizing Arduino Uno, PZEM-004T sensors, relay modules, and LabVIEW software integration for monitoring and controlling. The test results showed that the system successfully monitored electrical parameters (voltage, current, power, and frequency) with a good level of sensor accuracy (error ≤0.03%), and was able to activate automatic protection against under/over voltage and over current conditions  with a fast response according to the set limit. These findings confirm that mini SCADA is not only feasible as a means of practical learning, but also has the potential to be an early model for the implementation of small-scale distribution control such as microgrids. In addition, this study provides empirical evidence that simple hardware integration with open-source software can result in efficient and applicable control systems. In conclusion, this study makes a significant contribution to expanding the understanding of SCADA integration with distribution relays, while opening up further research opportunities related to system communication optimization to reduce response delays and improve operational resilience in the future..This study aims to develop  a mini SCADA system  as a simpler and more affordable alternative solution for educational and research purposes, especially in the control of relays in distribution system modules. Design and implement  of a mini SCADA prototype are able to control the relay in real-time while evaluating the performance of the system in terms of response speed, control accuracy, and operational reliability. The research adopts both quantitative and qualitative approach with laboratory experiment methods at Malikussaleh University, utilizing Arduino Uno, PZEM-004T sensors, relay modules, and LabVIEW software integration for monitoring and controlling. The test results showed that the system successfully monitored electrical parameters (voltage, current, power, and frequency) with a good level of sensor accuracy (error ≤0.03%), and was able to activate automatic protection against under/over voltage and over current conditions  with a fast response according to the set limit. These findings confirm that mini SCADA is not only feasible as a means of practical learning, but also has the potential to be an early model for the implementation of small-scale distribution control such as microgrids. In addition, this study provides empirical evidence that simple hardware integration with open-source software can result in efficient and applicable control systems. In conclusion, this study makes a significant contribution to expanding the understanding of SCADA integration with distribution relays, while opening up further research opportunities related to system communication optimization to reduce response delays and improve operational resilience in the future.